1997
DOI: 10.1084/jem.186.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Eotaxin Generation and Its Relationship to Eosinophil Accumulation in Allergic Airways Disease: Analysis in a Guinea Pig Model In Vivo

Abstract: Challenge of the airways of sensitized guinea pigs with aerosolized ovalbumin resulted in an early phase of microvascular protein leakage and a delayed phase of eosinophil accumulation in the airway lumen, as measured using bronchoalveolar lavage (BAL). Immunoreactive eotaxin levels rose in airway tissue and BAL fluid to a peak at 6 h falling to low levels by 12 h. Eosinophil numbers in the tissue correlated with eotaxin levels until 6 h but eosinophils persisted until the last measurement time point at 24 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
166
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(193 citation statements)
references
References 41 publications
22
166
1
4
Order By: Relevance
“…Likewise, exposure of IL-5 gene knockout mice to aerosolized Ags caused an ablated eosinophil recruitment into the lungs (42). The results from both in vitro and in vivo investigations also suggest that eotaxin and IL-5 may act cooperatively and synergistically to promote the recruitment of eosinophils into tissues (29,30,43,44). In mice, eotaxin-induced recruitment of eosinophils to the lung and skin was only consistently observed in IL-5-transgenic mice, which have elevated levels of IL-5 and a pronounced basal blood eosinophilia (29,30).…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, exposure of IL-5 gene knockout mice to aerosolized Ags caused an ablated eosinophil recruitment into the lungs (42). The results from both in vitro and in vivo investigations also suggest that eotaxin and IL-5 may act cooperatively and synergistically to promote the recruitment of eosinophils into tissues (29,30,43,44). In mice, eotaxin-induced recruitment of eosinophils to the lung and skin was only consistently observed in IL-5-transgenic mice, which have elevated levels of IL-5 and a pronounced basal blood eosinophilia (29,30).…”
Section: Discussionmentioning
confidence: 96%
“…There is some limited data. RAN-TES expression has been observed in airway smooth muscle cells in airway bronchial biopsies from healthy volunteers as well as from asthmatic subjects [26], while eotaxin immunoreactivity is reported in airway smooth muscle of airways from patients with asthma, with weaker staining in those from healthy volunteers [32], and of airways from guinea-pigs following allergen challenge [82]. Therefore, the production of chemokines in the airway smooth muscle may allow a gradient of chemotaxis to exist between the microvasculature and the airway smooth muscle, allowing T-cells, eosinophils, neutrophils, and monocytes to accumulate around smooth muscle cells.…”
Section: Effects Of Inflammatory Factors On Airway Smooth Muscle Contmentioning
confidence: 99%
“…24 IL-5 was originally discovered in guinea pigs and found to be responsible for allergen-induced eosinophil accumulation in the lungs. 25 Eotaxin is an eosinophil-selective chemoattractant that has been identified as a potent activator of eosinophils, inducing eosinophils to generate superoxide and release granule proteins. Early studies suggested that eosinophil recruitment in allergic reactions was regulated by Th2 lymphocytes and that eotaxin production was T celldependent.…”
Section: Arsenic Trioxide and Asthma K-h Chu Et Al 378mentioning
confidence: 99%